First record of Pheidole indica Mayr, 1879 (Hymenoptera, Formicidae) in Algeria (North Africa) and its relationships with local Hemipterans - N. Oussalah; N. Guerrouche; Y. Agagna; X. Espadaler; S. Salem Attia; M. Biche (Arxius de Miscel-lània Zoològica)
Primer registre de Pheidole indica Mayr, 1879 (Hymenoptera, Formicidae) a Algèria (nord d’Àfrica) i les seves relacions amb els hemípters locals